The prevalence of asthma and other allergic diseases in a province of Turkey - Küçüködük, Şükrü; Aydın, Murat; Çetinkaya, Feyzullah; Dinç, Hüseyin; Gürses, Nuran; Saraçlar, Yıldız (The Turkish Journal of Pediatrics, 1996)
To document the prevalence of asthma and other allergic disorders among children, a questionnaire study involving 3,118 children aged six to 14 years was done. The overall prevalence of allergic diseases was 27.4 percent and the prevalence of each disorder was as follows: rhinitis 11 percent, asthma 10.2 percent, conjunctivitis 7.1 percent, and skin diseases 6.3 percent. Atopic diseases were reported most commonly among the families of children with allergic rhinitis. When compared with internal regions of Turkey, the prevalence of allergic diseases was found to be very high. It was concluded that allergic diseases are an important health problem among children in our region.
Keywords: allergic diseases; asthma; childhood; prevalence